Faktor-Faktor Penentu Kepuasan Kerja Karyawan Kontrak pada Hotel Artotel Sanur Bali - Anggriana, Siti; Ariani, Ni Made; Pertiwi, Putu Ratih (Jurnal Kepariwisataan dan Hospitalitas; Vol 5 No 1 (2021): Vol.5,No.1,2021, 2021)
This research was conducted at Artotel Sanur Hotel which was motivated by the fact, employees of Artotel Sanur have achieved job satisfaction as evidenced by the low turnover rate below 10%, the high number of good comments, the average appraisal assessment is good category, the results of survey were quite satisfactory conducted by Artotelgroup. Against this background, this study intends to find out what factors are and what is the dominant factors that determine job satisfaction of employees at these Hotel. The type of data is qualitative and quantitative, with primary and secondary data sources, collected through observation, questionnaires, interviews, and documentation. Determination of informants by purposive sampling, determination of samples with saturated/census totaling 63 respondent. The analysis technique used is likert scale and confirmatory factor analysis. The results showed that there were four factors, namely: individual factors and company policies; social and promotional factors; organizational and management factors; supervisor and communication factors. Factor 1 has an eigenvalue value of 45,360%, factor 2 has an eigenvalue value of 1,570%, factor 3 has an eigenvalue value of 1,372%, factor 4 has an eigenvalue value of 1,210%. These four factors can explain 66,116%. The dominant factor is factor 1 which consists of 7 indicators namely pleasant work, challenging work, employee facilities, respect, appreciation, rules of performance and leave. Based on research result, the advice given to Artotel Sanur Hotel is that it always maintains and increases job satisfaction of contract employees, especially on these dominant factors.   Keywords: Job Satisfaction, Contract Employees, Hotels